Land policies for growth and poverty reduction / Klaus Deininger. - Deininger, Klaus W., 1962- (World Bank policy research report., 2003)
This volume synthesizes insights from the vast literature on land policy, taking due account of actual experiences in policy implementation, and suggests ways to design land policies that promote growth as well as poverty reduction.